Assessment Models in Physics Education: A Systematic Review of Diagnostic, Formative, and Authentic Approaches - M Deva Syah Mudra; Juniar Afrida (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2026)
The assessment in physics education plays a crucial role in understanding how well students grasp core concepts and apply their knowledge in real-life situations. This research explores various assessment models used in physics education to enhance student learning outcomes. The primary objective of this study is to examine the effectiveness of different assessment models, including diagnostic, formative, summative, and competency-based evaluations. Literature review method was employed to gather and synthesize relevant studies from academic databases such as Google Scholar and Science Direct. The results reveal that formative assessment is particularly effective in improving student engagement and learning by providing continuous feedback. Moreover, competency-based assessments offer a more comprehensive evaluation by considering cognitive, affective, and psychomotor aspects of student learning. Authentic assessments that simulate real-world tasks are also gaining traction for their ability to bridge theoretical knowledge and practical application. This study concludes by recommending a combination of these assessment models for optimal student development in physics education.